YTHDF3 modulates the progression of breast cancer cells by regulating FGF2 through m6A methylation - Gong, R. F.; Zhang, Z. H.; Sun, T. T.; Zhao, Y. X.; Fang, Wen (Frontiers in Cell and Developmental Biology, 2024)
The most prevalent RNA modification in mammalian mRNAs is N6-methyladenosine (m 6 A), which has been increasingly implicated in human tumorigenesis. However, the precise role of the m 6 A methylation, particularly its reader YTHDF3, in influencing downstream targets and their functions, thereby driving the malignant progression of breast cancer, remains ambiguous. In this study, we have identified a novel mechanism involving fibroblast growth factor 2 (FGF2). FGF2, a member of the fibroblast growth factor family, is directly targeted by YTHDF3. By binding to m 6 A-modified FGF2 mRNA, YTHDF3 enhances the translation of FGF2 and facilitates the translation process in an m 6 A-dependent manner. Consequently, this mechanism promotes tumor development and metastasis in breast cancer. Notably, breast cancer cells exhibit high levels of YTHDF3 expression, and the upregulation of YTHDF3 is associated with poor prognosis in breast cancer patients. Additionally, we observed elevated FGF2 protein levels relative to its RNA abundance in breast cancer, and a positive correlation between FGF2 protein expression and YTHDF3 levels in breast cancer patients. In conclusion, our findings reveal a novel YTHDF3-FGF2 axis that plays a critical role in breast cancer growth and warrants further investigation as a potential therapeutic target for cancer treatment.